Two-Factor Self-Esteem Improvement Program for Adolescents with Self-Esteem Problems - Mujiati, Sri; Kurniawati, Farida (Journal of Education Reseach and Evaluation, 2024)
Low self-esteem is a problem that often occurs in adolescent students. Another problem is that research examining the effectiveness of intervention programs still focuses on participants with clinical conditions. On the other hand, general public participation in educational contexts, for example teenage students, still needs to be improved. This research analyzes a two-factor self-esteem enhancement program for adolescents with self-esteem problems. With a single subject design, this study aims to examine the effectiveness of a two-factor intervention development program for adolescent students with self-esteem problems. The intervention program was prepared based on the intervention program from Mruk (2006) which is directed at developing feelings of worth and capability in adolescent students who have self-esteem problems. Program evaluation was carried out quantitatively and qualitatively using the Kirkpatrick and Kirkpatrick (2006) program evaluation guide. Data on changes in knowledge were measured using a questionnaire, while changes in behavior were measured using the Indonesian version of the Rosenberg Self-Esteem Scale adapted by Maroqi (2018). The research results show that this intervention program has a positive impact on the self-esteem of problematic adolescent students. There are changes in adolescent students' knowledge and behavior after participating in the intervention program. The results of this research can be a reference for practitioners who work with adolescent students, such as psychologists, school counselors and teachers, to develop further intervention programs to support the development of students' self-esteem.